فعالية مطوية إعلامية لتنمية الوعي الصحي لدى تلاميذ مرحلة التعليم المتوسط - حفيان, رانيا; غريبي, مروة (University of Eloued جامعة الوادي, 2023)
.The study aimed to identify the level of health awareness among middle school students from thesecond, third and fourth grades, in addition to identifying the differences in the level of healthawareness according to the variables of gender and level. They have to identify health awareness,which consists of (34) items, and after collecting the data, it was processed using the statisticalprogram spss.In order to study this, a brochure was prepared for the development of health awareness amongstudents, and this falls within the practical side, and after analyzing and discussing the results, theresults showed that the level of health awareness was average, and the two researchersrecommended the need for female teachers to focus while activating educational activities on the health side in order to develop health awareness among students And discuss topics dealing withhealth awareness and health awareness of various infectious diseases and ways to prevent them forthe safety of the body.
مذكرة ماستر في علوم التربية تخصص ارشاد وتوجيه
Keywords: الوعي الصحي، Sensibilisation à la santé, Health awareness